2016
DOI: 10.1088/0965-0393/24/5/055019
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulations of the mechanisms controlling the propagation of bcc/fcc semi-coherent interfaces in iron

Abstract: Molecular dynamics simulations have been used to study the effects of different orientation relationships between fcc and bcc phases on the bcc/fcc interfacial propagation in pure iron systems at 300 K. Three semi-coherent bcc/ fcc interfaces have been investigated. In all the cases, results show that growth of the bcc phase starts in the areas of low potential energy and progresses into the areas of high potential energy at the original bcc/fcc interfaces. The phase transformation in areas of low potential en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 31 publications
4
20
0
Order By: Relevance
“…Urbassek 23,63 and, more recently, Ou et al 24 . All these studies consider the motion of fcc-bcc interfaces with "flat" boundaries, i.e.…”
Section: Appendices Appendix a Further Comparison With Experimentsmentioning
confidence: 99%
“…Urbassek 23,63 and, more recently, Ou et al 24 . All these studies consider the motion of fcc-bcc interfaces with "flat" boundaries, i.e.…”
Section: Appendices Appendix a Further Comparison With Experimentsmentioning
confidence: 99%
“…Atomistic simulations methods such as molecular dynamics (MD), have evolved as a powerful tool to analyse the mechanisms which are difficult to observe experimentally. MD simulations have been used to study different aspects in Fe based alloys such as the fcc to bcc transformation at fault intersections by Sinclair et al [16] and in systems containing bcc/fcc interfaces [17,18,19]. Wang et al have studied temperature induced martensitic phase transformations in single crystal Fe-C alloys using MD simulations [20].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Thus, it has been found that grain boundaries [5,6], other planar defects such as stacking faults [7] and dislocations [8][9][10] may act as nucleation sites for the transformation. In addition, phase boundaries [11][12][13][14] and heterogeneous interfaces, such as with carbide phases [15], affect the transformation behavior; in these cases, of course, the crystal orientation at the interface is decisive.…”
Section: Introductionmentioning
confidence: 99%